Histomorphological Study of Major Organs in Mithun (Bos frontalis) - Chamuah, Jayanta Kumar; Deka, Anil; Borkotoky, Debojyoti; Sumi, Angughali Aheto; Singh, Mahak; Kumar, Harshit; Patil, Girish S. (International Journal of Bio-resource and Stress Management, 2025)
The study was conducted during (October–December) 2024 at ICAR National Research Centre on Mithun, Nagaland, India. This study investigated the histological features of skin, kidney, liver, lung, and heart tissues collected from adult mithun specimens. The mithun (Bos frontalis), a semi-domesticated bovine species native to mountainous regions of Northeast India, also known as Gayal or mountain cattle. Despite its cultural and economic significance, detailed histological data on mithun organs remained limited. Histological studies served as essential tools in veterinary science, providing detailed insights into tissue structure and function, which were fundamental for understanding normal physiology, identifying pathological changes, and supporting species-specific medical and conservation strategies. Post-mortem tissue samples were fixed in 10% neutral buffered formalin and processed using standard histological techniques. The skin displayed typical mammalian organization with epidermis (comprising stratum corneum, stratum lucidum, stratum granulosum, stratum spinosum, and stratum basale), dermis, and hypodermis. The kidney exhibited distinct cortical and medullary regions, with the cortex containing glomeruli, proximal convoluted tubules, and distal convoluted tubules. The liver was encapsulated by Glisson’s capsule with hepatocytes forming the parenchymal structure. The lung parenchyma consisted of alveoli lined with simple squamous epithelium, interspersed with bronchioles lined by simple cuboidal epithelium. Cardiac tissue revealed branched cardiac muscle fibers containing one or two centrally located nuclei, with characteristic intercalated discs between adjacent fibers. This study established baseline histological parameters for major organs in mithun, contributing valuable information for comparative anatomy, veterinary diagnostics, and conservation efforts.